THE POSSIBILITIES OF ARTIFICIAL INTELLIGENCE FOR FOREIGN LANGUAGE TEACHING (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article examines the potential of artificial intelligence (AI) in the processof foreign language teaching. Compared with traditional methods of learning andteaching foreign languages, the advantages of artificial intelligence technologies,including efficiency in language learning, individual approach and flexibility, arediscussed. The article also discusses the potential of artificial intelligence-basededucational platforms, the main problems in language learning and the role of artificialintelligence in overcoming them.
Keywords: artificial intelligence, foreign language teaching, language learning, educational technologies, individual approach, learning platforms, student motivation